The Effect of The Use of Limestone As a Cement Subtitution and Ceramic Waste or Tile As a Coarse Aggregate Subtitution in Concrete Mixtures to The Strength of Concrete Press - Acep Hidayat; Ahmad Faham (NAROTAMA UNIVERSITY, Indonesia, 2021)
Concrete is the result of the preparation of materials consisting of cement, aggregate and water. All the constituent materials of concrete are obtained from natural resources, which, if exploited continuously will be increasingly depleted. The use of waste as an added material or as a substitute material is a good alternative for mixing the building blocks of concrete. Extinguished lime is one of the materials for making cement where quenched lime is made without a fabrication process such as cement which produces waste during the fabrication period. As for ceramic or tile waste, it is one of the building wastes that cannot be used anymore so that ceramic waste can be used as a substitute for coarse aggregate in the concrete mixture. This study aims to determine the effect of using extinguished lime as a substitute for cement and ceramic or tile waste as a substitute for coarse aggregate in the concrete mixture on the compressive strength of concrete. This study used a cylindrical specimen measuring 15x30 cm as many as 40 samples from 4 mixed variations and added with 4 normal concrete samples which serve as benchmarks. This study used a mixture of lime substitute as much as 15%, and 25% by weight of cement, as well as ceramic or tile waste as much as 30%, and 60% of the weight of coarse aggregate. Where the concrete compressive strength test was carried out on day 28. The results of this study were that the resulting slump value was still in accordance with the mix design with a range between 60-180 mm with the highest slump value found in the variation of 15% lime + 60% ceramic waste, namely 15 cm.